(untitled) (TAMADDUN NURI JURNALI, 2025)
The article examines the shortcomings in the education of children with visual impairments and ways to correct them. A number of opportunities, recommendations and solutions to problems that need to be created for students involved in inclusive education are presented. The relevance of the development of inclusive education and its methodological recommendations.